ANALISIS YURIDIS KEKUATAN ALAT BUKTI KETERANGAN SAKSI ANAK DALAM TINDAK PIDANA PERSETUBUHAN (PENELITIAN PUTUSAN NOMOR: 17/PID.SUS.ANAK/2014/PN.TJK) - Satrio Hadi; Dina Sukardi (Fakultas Hukum Universitas Tulang Bawang, 2021)
The focus of research is on the strength of evidence for child witness testimony in criminal acts of sexual intercourse and the basis for judges' consideration in using child witness evidence in Decision Number: 17 / Pid.Sus.Anak / 2014 / PN.TJK. The objectives to be achieved are to analyze the strength of the evidence for child witnesses in the criminal act of sexual intercourse and to analyze the basis for judges' consideration in using evidence for child witnesses in Decision Number: 17 / Pid.Sus.Anak / 2014 / PN.TJK. The research method uses a normative and empirical approach. Based on the results of the research, it is known that the strength of evidence of child witness testimony in the crime of sexual intercourse in accordance with Decision Number: 17 / Pid.Sus.A child / 2014 / PN.TJK only acts as a guide or additional valid evidence and information that can strengthen the judge's conviction. to further prove the guilt of the accused, and can be used to prove the indictment of the Public Prosecutor. The victim witness was not sworn in because he was not yet 15 (fifteen) years old.